(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Cancer is a most serious health problem globally due to increased mortality. Deoxycytidine triphosphate pyrophosphatase (dCTPase) enzyme involved in cancer progression and cancer cell stemness and found over-expressed in breast cancer. This overexpression makes it of attractive target to discover new class of anticancer therapy. In the present work, we have selected piperazin-1-ylpyridazine derivatives as dCTPase inhibitors and performed molecular docking and dynamics simulations analysis to evaluate the binding pattern of selected compounds with target protein. Compound P21 has highest binding affinity towards dCTPase protein with -4.649 as Glide Gscore. In all compounds, only pyridazine and caboxamide nucleus involves in hydrogen bond formation and benzyl or phenyl nucleus involves in π-π stacking interaction. These observations provide the valuable lead for ligand based anticancer drug design.